Improving the Professionalism and Performance of Education Personnel through Compensation Management - Anis Zohriah; Machdum Bachtiar; Anis Fauzi; Ratu Vina Rohmatika; Puji Lestari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Compensation management still refers to rank, class, and seniority not based on its performance. Salaries are paid at the same value according to the scale, class and length of service but for the provision of current performance allowances have been calculated in different performance achievements. Compensation management for non-civil servants in State Madrasahs in Cilegon City has been adjusted to their respective DIPA budgets. The difference in compensation management that occurs in the six State Madrasahs of Cilegon City is the authority of each Madrasah Head. This will lead to differences in compensation between madrasas. This study uses a correlation method that aims to detect the degree of association of variables in a factor with variables in another based on the correlation coefficient that describes the degree of relationship between two or more variables. The results of this research concluded that there is a positive and significant relationship between the professionalism of education personnel and the performance of education personnel of the Cilegon City State Madrasah. This can be seen from the significance value of the professionalism of educational personnel with the performance of educational personnel of 0.00 which means it is smaller than the level of significance used, which is 0.05. It can also be seen from the correlation value of the calculation of 0.812 > r table 0.281 and can even be seen from the calculated value of 9.546 > t table 1.677. Compensation management has a very strong role in improving the professionalism of educational personnel. Keywords: Compensation Management, Professionalism Education, Education Personnel